USE OF PERSONNEL APPLICATIONS (KEPO) IN THE FRAMEWORK OF PERSONNEL DATA MANAGEMENT OF THE SOLOK CITY PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY (BKPSDM) - Sriyanti, Esi; Mursalini, Wahyu Indah; Dodo, Harius Lion (Universitas Ibn Khaldun Bogor, 2024)
This research aims to find out how the Analysis of the Use of Online Personnel Applications (KEPO) on Personnel Data Management, Personnel Agency and Human Resources Development (BKPSDM) in Solok City, in making a breakthrough in the digital world of employees throughout Solok City. The type of research used is descriptive qualitative. The data collection techniques used in this research are observation and documentation. The type of data used is qualitative and the data source uses primary data sources. The data analysis technique used in this research is a qualitative descriptive method. The employee data used in this research was 41 people, consisting of Head of Section, Head of Subdivision and General Functional Staff (BKPSDM). The research results show that a comparative analysis of employee absence management, before and after using the Kepo application to make a breakthrough in the digital world of employees throughout Solok City, can make data management easier. Most application processing systems initially followed a manual processing system design using a fingerprint machine so that the processing of personnel data was slow which could result in slow delivery of information. The use of the KEPO (Online Personnel) application, which is an application that will make it easier to carry out personnel administration, store personnel data digitally, and make the process of managing personnel administration easier compared to previously using a fingerprint machine for attendance is the right choice compared to others.